Bercerita sebagai Pendekatan Humanistik dalam Stimulasi Bahasa Anak - elise muryanti (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2020)
This article discusses the implementation of Story Telling method as humanistic learning in Finland Kindergartens. Language is one aspect of development that is stimulated early on. Humanistic learning is learning that optimizes the potential of children as humans. In storytelling activities, children fulfill their basic needs in self-actualization. In the learning activities seen children in Finland are actively involved in story telling and the teacher facilitates learning in accordance with the interests and children’s need.